1972
DOI: 10.1021/ic50113a036
|View full text |Cite
|
Sign up to set email alerts
|

New cyclodisilazane derivatives

Abstract: Cyclodisilazanes with mixed silicon-substituted groups {Cl(CH8)RSi[SiR(CH8)N]2SiR(CH3)Cl} can be prepared either by heating mixtures of [R(CH3)SiNH]3 and R(CH3)SiCl2 or by treating HN[Si(CH3)RCl]2 with butyllithium and heating the product. One or both of the methods are shown to be applicable where R is ethyl, vinyl, phenyl, or 3,3,3-trifluoropropyl as well as methyl. The properties of the intermediate cyclotrisilazanes and disilazanes as well as the dialkylamino derivatives of the cyclodisilazanes are describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
0
13
0
1
Order By: Relevance
“…The 1,3-bis(chloro-silyl)-2,4-dimethyl-2,4-diphenylcyclodisilazane 3 and 4 were synthesized by stepwise reactions as shown in Scheme 3. We found that nearly quantitative conversion to such cyclodisilazanes could occur at 70 C which offered a mild condition compared to the previously reported work [19,20]. When the ring-closure reaction of 1 or 2 was performed using an equivalent of n-BuLi in toluene, 3 was obtained in large quantities as a mixture of cis/trans isomers while 4 was formed as trans-cyclodisilazane.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…The 1,3-bis(chloro-silyl)-2,4-dimethyl-2,4-diphenylcyclodisilazane 3 and 4 were synthesized by stepwise reactions as shown in Scheme 3. We found that nearly quantitative conversion to such cyclodisilazanes could occur at 70 C which offered a mild condition compared to the previously reported work [19,20]. When the ring-closure reaction of 1 or 2 was performed using an equivalent of n-BuLi in toluene, 3 was obtained in large quantities as a mixture of cis/trans isomers while 4 was formed as trans-cyclodisilazane.…”
Section: Resultsmentioning
confidence: 53%
“…For these mixed phenyl-substituted cyclodisilazanes, isomeric structures probably appeared as a result of the transmission of substituent effects throughout the Si 4 N 2 skeleton which indicated that long-range coupling could occur through silicon in the structure C 6 H 5 SiCH 3 [19]. Of particular interest was the spectrum of 3, the mixture of cis/trans isomers was clearly observed in the 29 Si and 13 C NMR spectra.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…11 In this reaction, the yield of BcPTPC was highly influenced by the polarity of the solvents used. In nonpolar solvents such as the xylene-hexane mixture solvent, the ringclosure reaction of DCTPS can smoothly take place, and the yield of BcPTPC is high, nearly 73.2%.…”
Section: Synthesis Of Bcptpc and B H Ptpcmentioning
confidence: 98%